2016
DOI: 10.1200/jco.2015.64.8824
|View full text |Cite
|
Sign up to set email alerts
|

PROCLAIM: Randomized Phase III Trial of Pemetrexed-Cisplatin or Etoposide-Cisplatin Plus Thoracic Radiation Therapy Followed by Consolidation Chemotherapy in Locally Advanced Nonsquamous Non–Small-Cell Lung Cancer

Abstract: Pemetrexed-cisplatin combined with TRT followed by consolidation pemetrexed was not superior to standard chemoradiotherapy for stage III unresectable nonsquamous non-small-cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
274
3
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 388 publications
(308 citation statements)
references
References 30 publications
16
274
3
6
Order By: Relevance
“…The preliminary results showed that despite the high anticancer activity of pemetrexed relative to the other drugs, there were no differences in mOS (26.8 months vs. 25 months), and 3-year survival rates (40% vs. 37%) between the pemetrexed plus cisplatin group and the etoposide plus cisplatin group. The toxicity profile differed in the two groups, and a significantly lower incidence of drug-related grade ≥ 3 AEs was found in the pemetrexed group compared with the etoposide group (Senan et al 2015). An early study revealed that combination treatment with cisplatin and 5-FU may cause synergistic cytotoxicity in NSCLC cells (Tsai et al 1993).…”
Section: Discussionmentioning
confidence: 92%
“…The preliminary results showed that despite the high anticancer activity of pemetrexed relative to the other drugs, there were no differences in mOS (26.8 months vs. 25 months), and 3-year survival rates (40% vs. 37%) between the pemetrexed plus cisplatin group and the etoposide plus cisplatin group. The toxicity profile differed in the two groups, and a significantly lower incidence of drug-related grade ≥ 3 AEs was found in the pemetrexed group compared with the etoposide group (Senan et al 2015). An early study revealed that combination treatment with cisplatin and 5-FU may cause synergistic cytotoxicity in NSCLC cells (Tsai et al 1993).…”
Section: Discussionmentioning
confidence: 92%
“…Unresectable disease should preferentially be treated with concomitant chemo-radiotherapy (cCTRT), the most commonly used regimen being cisplatin with etoposide. Randomized trials testing modern platinum-based doublets, such as cisplatin plus pemetrexed and cisplatin plus vinorelbine, have failed to demonstrate superiority over that doublet, even though the toxicity profile appeared to be better with new agents 30,31 . …”
Section: Pharmacological Treatments Early Stagesmentioning
confidence: 99%
“…Currently, the clinical outcomes are still unsatisfactory, and the 5-year survival rate of is approximately 20%. In recent published studies, attempts to improvement of the radiation dose (RTOG 0617) and use of a new generation of chemotherapy regimen (PROCLAIM) failed to demonstrate survival benefits compared with concurrent platinum-based doublet chemoradiotherapy conventionally used in clinical practice (47,48). Uncertainties resulted from high treatment-related toxicities and poor completion rates of chemoradiotherapy in these trials should be rethink profoundly in future studies, and further improvement in locally advanced NSCLC will require the development of more effective combined modality therapies with low toxicities.…”
Section: Management Of Local Advanced Nsclc With Tki and Radiotherapymentioning
confidence: 99%